Oil/water separation by super-hydrophobic wastepaper cellulose-candelilla wax cryogel: a circular material-based alternative - Romero-Montero, A.; Rosas-Melendez, S. A.; Valencia-Bermúdez, J. L.; Nuñez-Tapia, I.; Piña-Barba, M. C.; Melgoza-Ramírez, L. J.; Leyva-Gómez, G.; Del Prado-Audelo, M. L. (Frontiers in Materials, 2023)
One of the most attractive fields for cellulose aerogels is water remediation, basically in the pollutant's adsorption and oil/water separation. There are different sources to extract cellulose, but the extraction from paper waste is an excellent option for impulse circular materials applications. Here, we obtained cellulose from office waste paper through a simple alkali method and used it to fabricate an aerogel by freeze-drying based on the materials' circularity. To increase lipophilicity, the aerogel was modified using two different coatings: polycaprolactone (WOPP) and candelilla wax (WOPW), extracted from a Mexican plant. To our knowledge, this is the first time that candelilla wax has been reported as aerogel modification. The aerogels were analyzed by several physicochemical techniques such as Scanning Electronic Microscopy, Infrared spectroscopy, and thermal analysis. The highly porous aerogels showed a density of around 0.1 g/cm 3 and a fibrous structure. Furthermore, the contact angle of the aerogels was measured to compare the hydrophobicity of the surfaces, showing values around 120° in the modified aerogels compared with the hydrophilic behavior of pristine cellulose aerogel. The achieved recycled mineral oil absorption capacity for WOPW was 6.1 g/g, while for WOPP was 4.88 g/g. Thus, we obtained a natural coating aerogel with a high water/oil separation potential.